2022
DOI: 10.46799/jsa.v3i1.380
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of The Influence of Exchange, Inflation, Gross Domestic Product, Interest Rate, and The Amount of Money Circulation On The LQ45 Index In The Indonesia Stock Exchange Between 2016-2020

Abstract: The objective of this research was to analyze the short and the long-run relationship between five macroeconomics variables such as exchange rate, inflation, Gross Domestic Product (GDP), SBI rate, and money supply to examine their influence on the LQ45 stock price index. The data sample used in this study is monthly time series data from January 2016 to December 2020. This study used Vector Error Correction Model to analyze the problem. The result shows that in the short run (1 month ago), exchange rate, infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…An increase in money supply can lead to an increase in consumer spending and business investment, which can boost corporate profits and, subsequently, stock prices. However, if an increase in money supply is not accompanied by an increase in production, it can lead to inflation, which can adversely affect the stock price index (Nurmansyah & Thamrin, 2022;Karimova et al, 2022). Conversely, a decrease in money supply may lead to a decrease in consumer spending and business investment, potentially impacting corporate profits and stock prices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in money supply can lead to an increase in consumer spending and business investment, which can boost corporate profits and, subsequently, stock prices. However, if an increase in money supply is not accompanied by an increase in production, it can lead to inflation, which can adversely affect the stock price index (Nurmansyah & Thamrin, 2022;Karimova et al, 2022). Conversely, a decrease in money supply may lead to a decrease in consumer spending and business investment, potentially impacting corporate profits and stock prices.…”
Section: Introductionmentioning
confidence: 99%
“…Not only that, the three variables also show the dynamics of shortterm relationships with a fairly high speed of adjustment towards equilibrium every month. Nurmansyah & Thamrin (2022) analyzed the shortterm and long-term relationship between five macroeconomic variables such as exchange rate, inflation, Gross Domestic Product (GDP), SBI rate, and money supply to test their influence on the LQ45 stock price index. The results showed that in the short term (1 month ago), the exchange rate, inflation, Gross Domestic Product (GDP), SBI rate, and money supply had no effect on the LQ45 stock price index.…”
Section: Introductionmentioning
confidence: 99%